Kontekstualisasi Hukum Keluarga Islam di Indonesia - Qodariah Barkah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2018)
The protection of the human rights of women and children can be noticed in the law or constitution that promotes the reform of family law in Indonesia, particularly for Muslims. It aims to assure legal certainty for the lives of women, wives, mothers, and children to be protected. Islamic family law in Muslim countries, especially in Indonesia, highlights a different position for Muslims since it is pivotal to maintain the family’s security and comfort. This paper tries to elaborate the implementation of Islamic Family Law stipulated in the Law Number 1 of 1974 concerning Marriage and the Compilation of Islamic Law. A qualitative design was employed in this current study. The collected data were retrieved from books, journal articles, and other references relevant to this study as the primary data, whereas the secondary ones were obtained from the literature related to this study. The research findings expose that Islamic family law in Indonesia still requires to be greatly taken into account so that the well-established goals of Muslim families can be achieved to assure the women and children rights, specifically for their everyday lives and inheritance.